Digital post-harvest transformation: Implementing IoT-based grain drying to enhance farmer welfare in Ngarum Village - Mar’atullatifah, Yulaikha; Iswavigra, Dwi Utari; Wicaksono, Nicky Gilang; Prasetyo, Deny; Suyahman, Suyahman; Wicaksono, Ardy; Mursalim, Mursalim; Mahmudah, Himmatunnisak; Mustofa, Mustofa; Faruq, Muhamad; Puspasari, Novela Putri (Community Empowerment, 2025)
Ngarum Village has a significant grain production potential of 43,459 tons per year, yet farmers face challenges with traditional drying processes that are vulnerable to sudden weather changes. This condition often leads to degraded grain quality and lower market prices. This community service program aims to increase productivity and economic value through the implementation of an Internet of Things (IoT)-based rain detection system. The methods include technical training, appropriate technology implementation, and continuous mentoring. Results indicate that IoT technology successfully maintains grain moisture at an optimal level of 14%, reduces post-harvest losses by 10%, and achieves an 80% adoption rate among farmers. Furthermore, the digitalization of farm management has increased the grain's selling price by 10%. The application of this technology has proven effective in improving post-harvest efficiency, enhancing harvest data accountability, and supporting sustainable farmer welfare.